2008
DOI: 10.1007/s11669-008-9463-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Assessment of the La-Cr-O System

Abstract: The La-Cr and the La-Cr-O systems are assessed using the Calphad approach. The calculated La-Cr phase diagram as well as LaO 1.5 -CrO 1.5 phase diagrams in pure oxygen, air, and under reducing conditions are presented. Phase equilibria of the La-Cr-O system are calculated at 1273 K as a function of oxygen partial pressure. In the La-Cr system reported solubility of lanthanum in bcc chromium is considered in the modeling. In the La-Cr-O system the Gibbs energy functions of La 2 CrO 6 , La 2 (CrO 4 ) 3 , and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
(135 reference statements)
1
15
0
Order By: Relevance
“…Thus, we believe that the experimental increase of d from 1173 to 1073 K might be too small, possibly caused by equilibration difficulties due to slow diffusion at these lower temperatures. 69,70 in the case of LaCrO 3 , 20 we did not obtain satisfying results in higher-order perovskites, most likely due to more complex interactions that cannot be sufficiently described by the model. Since the magnetic transitions are low temperature features, their modeling was omitted without consequences for the applicability of the database for SOFC.…”
Section: La 1àx Sr X Cro 3àdmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, we believe that the experimental increase of d from 1173 to 1073 K might be too small, possibly caused by equilibration difficulties due to slow diffusion at these lower temperatures. 69,70 in the case of LaCrO 3 , 20 we did not obtain satisfying results in higher-order perovskites, most likely due to more complex interactions that cannot be sufficiently described by the model. Since the magnetic transitions are low temperature features, their modeling was omitted without consequences for the applicability of the database for SOFC.…”
Section: La 1àx Sr X Cro 3àdmentioning
confidence: 61%
“…No quaternary phases or solid solutions were found in the Sr-Mn-Cr-O oxide system. 16 Previous assessments of the La-O, Cr-O, La-Cr-O, and Cr-Mn-O oxide databases are adopted from Povoden et al, [17][18][19][20][21] with some modifications denoted in the supplement file to this paper, LSCM_v1.0.tcm (ThermoCalc macrofile), and the La-Sr-Mn-O oxide database is taken from Grundy et al, [22][23][24][25][26][27] also with the following slight modification: Grundy et al 23,24 allowed Mn 31 on the A-site of LSM to reproduce experimental oxygen nonstoichiometries under low oxygen partial pressures. Due to large differences between the ionic radii of La 31 and Mn 31 and possible coordination numbers (1.5 Å for 12-fold coordinated La 31 , 0.785 Å for at maximum 6-fold coordinated Mn 31 ), 28 we omit Mn 31 on the A-site.…”
Section: Assessment Of Oxide Subsystemsmentioning
confidence: 99%
“…Regarding the thermodynamics of the La-Cr-O system, a recent study of thermodynamic calculations using CALPHAD [31] showed that LaCrO 3 is stable up to 1000°C in atmosphere ranging from pure O 2 to PO 2 = 10 -16.1 Pa. On the other hand, La 2 CrO 6 was shown to form within a wide temperature range above 7000°C at PO 2 at and above 10 5 Pa. While the SOEC stacks are operated at atmospheric pressure, the local PO 2 in anode and contact layer of the cells can be greater than 10 5 Pa because of the generation and evolution of O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The thermodynamic descriptions for the 3 binary sub-systems (Co-O, Cr-O, Co-Cr) are from Chen et al [19], Povoden et al [29], and Kusoffsky and Jansson [30]. The oxygen solubilities in pure Co and pure Cr were modeled by Chen et al [19] and Povoden et al [29], respectively. No information on the oxygen solubility in the Co-Cr alloy is available in the literature.…”
Section: Thermodynamic Modelingmentioning
confidence: 99%
“…There are nine end-members according to the current model of the cubic spinel phase. The four Gibbs energies of the end-members belonging to the [Co 2+ , Co 3+ ] 1 (Co 2+ , Co 3+ ) 2 O 4 system have been taken from Chen et al [19], and the Gibbs energy of the [Cr 2+ ] 1 (Cr 3+ ) 2 O 4 end-member has been taken from Povoden et al [29]. The Gibbs energies of the four end-members [ …”
Section: Solid Oxidesmentioning
confidence: 99%